Postradiotherapy Outcome on Cervical Cancer Stage IIIB Patients with and without Paraaortic Lymph Nodes Enlargement: Hasil Pascadiadioterapi pada Pasien Kanker Serviks Stadium IIIB dengan dan tanpa Pembesaran Nodus Paraaorta - Fitriyadi Kusuma; Sahat B. Matondang; Laila Nuranna; Gatot Purwoto; Oni Khonsa; Purnomo Hyaswicaksono (Indonesian Journal of Obstetrics and Gynecology, 2021)
Objective : To determine whether there are differences in clinical response after radiotherapy and 1 year survival in patients with advanced cervical cancer with and without enlargement of PALN.Method : An observational analytic study using a retrospective cohort method was done using consecutive sampling. The subjects of this study were all women with a primary diagnosis of stages IIB to IVB cervical cancer who came to the gynecological oncology clinic of Dr. Cipto Mangunkusumo National General Hospital and underwent MRI examination before undergoing treatment in January 2016 to May 2017Results: Among 76 subjects studied, there were 4 (5.1%) subjects who had enlarged PALN. There were no significant differences between the enlargement status of PALN and age (p = 0.829), age of first sexual intercourse (p = 0.33), parity (p = 0.642), mass diameter (p = 0.777). Patients with PALN enlargement have 2.13 times risk of having negative radiotherapy outcome (p = 0.02, OR 2.13, CI95% 1.12 – 4.07). There was no difference in 1-year survival between patients with and without enlargement of PALN (median 201 vs. 293, p = 0.072).Conclusion: Patients with PALN enlargement have increased risk of having negative radiotherapy outcome (p < 0.05). There were no differences in 1 year survival between patients with advanced cervical cancer with enlargement PALN.Keywords : cervical cancer, lymph node enlargement, paraaortic, radiotherapy. Abstrak Tujuan: Mengetahui adakah perbedaan respon klinis pascaradioterapi dan kesintasan 1 tahun pada pasien kanker serviks stadium lanjut dengan pembesaran KGB paraaorta dibandingkan tanpa pembesaran KGB paraaorta.Metode: Penelitian ini merupakan penelitian analitik observasional dengan menggunakan metode kohort retrospektif. Pengambilan sampel dilakukan dengan cara pengambilan sampel berturut-turut. Subyek penelitian ini adalah semua perempuan dengan diagnosis primer kanker serviks stadium IIB hingga IVB yang datang ke poliklinik Onkologi Ginekologi RSUPN Dr. Cipto Mangunkusumo dan menjalani pemeriksaan MRI sebelum dilakukan terapi pada bulan Januari 2016 hingga Mei 2017.Hasil: Dari 76 subjek yang diteliti, didapatkan sebanyak 4 (5,1%) subyek yang mengalami pembesaran KGB paraaorta. Tidak didapatkan perbedaan yang bermakna antara status pembesaran KGB paraaorta dan usia (p = 0,829), usia hubungan seksual pertama (p = 0,333), paritas (p = 0,642), dan diameter massa (p = 0,777). Pasien dengan pembesaran KGB paraaorta memiliki risiko 2,13 kali lipat (p = 0,02, OR 2,13, IK95% 1,12-4,07) memiliki risiko respon terapi negatif. Tidak terdapat perbedaan kesintasan 1 tahun antara pembesaran KGB paraaorta dan tidak (median 201 vs. 293, p = 0,072).Kesimpulan Pasien dengan pembesaran KGB paraaorta memiliki risiko lebih tinggi mengalami respon radioterapi negatif. (p < 0,05). Tidak terdapat kesintasan 1 tahun antara pasien kanker serviks stadium lanjut dengan dan tanpa pembesaran KGB.Kata kunci: kanker serviks, paraaorta, pembesaran KGB, radioterapi.